Revitalizing Governance: How West Java’s SAKIP Transformed Public Accountability Post-COVID-19 - Werang, Maria Lusiana Florentin; Rizki, Mia; Yolandasari, Priscilia; Werang, Nicolaus Petrus Likuwatan (Ilomata International Journal of Social Science, 2025)
In Indonesia’s public sector, the Performance Accountability System (SAKIP) is a vital governance mechanism, and its post-COVID-19 concretization necessitates thorough examination, especially at the provincial level. Next move, given that public accountability remains paramount in governance, this study investigates SAKIP’s implementation in West Java, specifically focusing on institutional strengthening and oversight mechanisms. Furthermore, a descriptive qualitative approach was used, whereby secondary data was collected from official documents and media reports to evaluate SAKIP’s effectiveness. Consequently, the analysis reveals that the West Java Provincial Government has demonstrated significant improvements, as evidenced by consistent increases in SAKIP scores from 2019 to 2022, while the integration of robust oversight mechanisms has effectively facilitated meaningful public scrutiny and engagement. Subsequently, several key outcomes emerged, including enhanced institutional performance metrics, successful establishment of transparent oversight mechanisms, and strengthened government-public relationships. Moreover, the implications provide practical insights for policymakers while demonstrating SAKIP’s dual role as both a compliance tool and a catalyst for improved governance.